Evaluation Des Attaques De Termites (Isoptera Brulle, 1832) Sur Quatre Essences Forestieres D’importance Economique Au Togo (Afrique De L’ouest) - Gbenyedji, Jean Norbert B.K.; Kasseney, Boris Dodji; Nyamador, Seth Wolali; Sanbena, Banibéa Bassan; Kokutsè, Adzo Dzifa; Kokou, Kouami; Glitho, Isabelle Adolé (European Scientific Journal, ESJ, 2016)
Termites are one of the most abundant invertebrates in tropical ecosystems, where they play a major ecological role in litter decomposition. Despite their important role, termites can cause considerable damage to wood structures in most tropical countries. The aims of this study was to evaluate termite attack in four economically important species in Togo including Antiaris africana Engl (Moraceae), Pterocarpus erinaceus Poir (Fabaceae), Triplochiton scleroxylon Schum (Malvaceae) (all local species) and teak or Tectona grandis Linné (Lamiaceae). For the latter species, termites were infested on 83.49% of 630 feet examined. However, the rate and type attacks differ from one plantation to another. On the studied forest species, termites were collected on about 97% of Triplochiton scleroxylon feet. For this species, at least 31% of examined feet have had their wood attacked. For the other two species, Pterocarpus erinaceus and Antiaris africana respectively about 80% and 67% of examined feet were attacked by termites. Amitermes evuncifer, Ancistrotermes guineensis and Microtermes lepidus were species of termite often harvested from trees examined. However the last two species namely A. guineensis and M. lepidus are encountered on the bark of trees inside veneers unlike A. evuncifer harvested in the heart of the wood. Therefore, the latter species deserves special attention as likely to cause serious damage not only to these species but also other species not taken into account in this study. It is therefore necessary to consider adequate control methods against these species.